التدين وعلاقته بالجمود الفكري الدغماتية لدى طلبة جامعة الكوفة - الصراف, لبنى عبد الرسول (Journal of Kufa Studies Center, 2011)
مستخلص البحث: ان الدين حاجة ضرورية للانسان فهو له الدور الكبير في الإرشاد والنهوض بالبشرية ويمكنه الاسهام بشكل فعال في العثور على حلول مناسبة للمشكلات القائمة. فهناك العديد من المشكلات المعاصرة التي لا يمكن حلها الا بالتعاون بين الأطراف المعنية بصفة عامة والدينية بصفة خاصة. ومن بين هذه المشكلات الملحة في عالمنا المعاصر على سبيل المثال لا الحصر مشكلات التطرف والتعصب والعنف والارهاب والجريمة المنظمة ..الخ، والتي يكون اساسها الجمود الفكري. ان عراقنا الحبيب اليوم يتعرض الى مختلف اصناف هذه المشكلات ومن مختلف الجهات وبالاخص التي تنضوي تحت غطاء الدين. فالإنسان هو المدخل لدراسة الاديان، وان العقل هو المدخل للايمان والتدين . ويكتسب البحث الحالي اهمية من خلال تناوله لمرحلة مهمة من حياة الطالب وهي المرحلة الجامعية وهو يهدف الى:- 1.قياس التدين لطلبة كلية الآداب. 2.قياس الجمود الفكري لطلبة كلية الآداب. 3.التعرف على العلاقة بين التدين والجمود الفكري لدى طلبة كلية الآداب. وقد اختيرت العينة بطريقة عشوائية حيث بلغت (130) طالباً ومن التخصصات الانسانية الآتية : (اللغة العربية، التاريخ، الجغرافية، الفلسفة، اللغة الانكليزية، المجتمع المدني)، ولتحقيق اهداف البحث اعتمدت الباحثة على مقياسين كل على حده، فكانت عدد الفقرات المميزة لمقياس التدين (60) فقرة مميزة، في حين بلغت الفقرات المميزة لمقياس الجمود الفكري (40) فقرة مميزة. تم الاعتماد على المقياسين بعد التحقق من صدقهما وثباتهما في القياس. وقد أسفرت أهم نتائج البحث الحالي إلى ما يأتي:- 1.ان الطالب الجامعي لا يمتاز بالتدين الشديد وانه معتدل في تدينه. 2.ان الطالب الجامعي يعاني نوعاً ما من الجمود الفكري وقد يكون هذا بسبب الظروف الغير طبيعية التي مر بها العراق . 3.هناك علاقة بين التدين والجمود الفكري الا ان هذه العلاقة بالسالب أي انه كلما زادر التدين قل الجمود الفكري. 4.التشجيع على التحرر من قيود الافكار البالية والتقاليد الرجعية مما يجعلها جامدة وغير قابلة للتغيير. 5.التوعية الدينية الحديثة وبما يتناسب مع الحياة الاجتماعية والسياسية الحديثة. That religion is an urgent need for humans is a significant role in guidance and advancement of humanity and can contribute effectively to find appropriate solutions to existing problems. There are many contemporary problems can be solved only through cooperation between the parties concerned in general and religious in particular. Among the pressing problems of our contemporary world, for example, but not the problems of extremism and intolerance, violence, terrorism and organized crime, etc. .., and be based on intellectual stagnation. That our beloved Iraq today are exposed to various classes of these problems from different bodies and in particular, which falls under the guise of religion. Man is the entrance to the study of religions, and that reason is the entrance to the faith and religion. The current research is gaining importance by addressing the important stage of the life of a student Undergraduate It aims to: - 1.Measuring religiousness of students of the Faculty of Arts. 2. Measuring intellectual stagnation of the students of the Faculty of Arts. 3. Identify the relationship between religiosity and intellectual stagnation among the students of Faculty of Arts. The sample chosen randomly, hitting (130) students and multidisciplinary approach to humanity as follows: (Arabic language, history, geography, philosophy, English, civil society) and to achieve the objectives of the research the researcher on two measurements each alone, was the number of paragraphs unique to the measure of religiosity (60), paragraph distinctive, while the paragraphs characteristic scale of intellectual stagnation (40), paragraph distinctive. Relied on the scales after verification of the sincerity and endurance in the measurement. The most important outcomes have resulted in the current search to the following: - 1. The university student is not religiosity is characterized by severe and a moderate in his religion. 2.The university student is suffering some sort of intellectual stagnation may be due to abnormal circumstances experienced by Iraq. 3.There is a connection between religiosity and intellectual stagnation, but this relationship that whenever any negative religiousness Zadr Say intellectual stagnation. 4.Encouragement to break free of outdated ideas and traditions, making it the retro rigid and not subject to change. 5.Religious awareness of modern and commensurate with the social and political life of modern